Analisis miskonsepsi pengenalan pada pecahan menggunakan media pembelajaran - Een Unaenah; Alfira Fazriandina; Siti Robiah Al Damiyah Al Damiyah; Yanti Ardia Ningsih; Fitri Alia; Nesfi Berliana; Alma Novianti Gunawan (Educatif Journal of Education Research, 2020)
Research is motivated by misconceptions that often occur because students' learning styles are relevant so that it is difficult to be equalized because students have different levels of understanding in each individual. And the concept can be overcome by applying the method of learning learning by doing, by choosing the right media so that students can get down directly in the learning process, and can be a separate motivation for students who are passive in class with students who are too active in class.